Medicinal Uses of Castor Plant - Ramanjaneyulu, A. V.; Gopal, N. Madana (International Journal of Economic Plants, 2015)
Castor (Ricinus communis L.) is one of the ancient and important non-edible oilseed crops. Different parts of castor plant gained importance because of their utilization for medicinal uses. The leaf can be used in the treatments related to antiviral, biliousness, burns, ear and head ache, malaria and night blindness while stem is used to treat cancer and hypoglycemia. The flowers can be utilized against glandular and vaginal pain. Fruits are used for curing tumors, treating piles, liver and spleen diseases. Root bark is used as purgative, in abortion, ascites, asthma, bronchitis, carination, hypoglycemia, leprosy, pains, rectum and rheumatism diseases. Hence, an attempt was made to document innumerable uses of castor medical sector in medical field.